2013
DOI: 10.1136/heartjnl-2013-303767
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and stroke risk in patients with atrial fibrillation

Abstract: Despite a reduced prevalence of AF among South Asian patients, their risk of stroke is higher than for white patients or black African/Caribbean patients in association with diabetes, cardiovascular disease, and hypertension. Under-prescription of anticoagulation persists in all ethnic groups, a deficit most pronounced in the elderly. Use of the CHA2DS2VASc score would enhance optimal management in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…8 In common with other investigators we found anticoagulation prescribing rates of 50%, and that prescribing was poorly related to the risk of stroke.…”
Section: 3supporting
confidence: 65%
“…8 In common with other investigators we found anticoagulation prescribing rates of 50%, and that prescribing was poorly related to the risk of stroke.…”
Section: 3supporting
confidence: 65%
“…42 In Singapore, there was a higher prevalence of family history of vascular disease in SA as compared to Chinese (OR 2.17, p<0.01). 44 …”
Section: Ii) Etiologymentioning
confidence: 93%
“…39,42 Among stroke survivors in the UK, SA had nearly double the rates of DM (50.3% vs. 29.8% respectively, p=<0.001) and approximately 1/3 the rate of atrial fibrillation (11.8% vs. 34.8% respectively, p=<0.001) compared to Europids. 43 The lower rates of atrial fibrillation may be in part attributed to the younger age of SA with stroke.…”
Section: Ii) Etiologymentioning
confidence: 96%
“…2,19 Attempts since 2007 by the NHS Improvement programme using the GRASP-AF software tool to improve anticoagulation had limited success. 36 About one-quarter of practices in England UK participated, and anticoagulation increased from 49.3% to 54.7% over the period 2009-2012.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…[13][14][15] Fewer older patients with AF are prescribed anticoagulants, and anticoagulant use is poorly related to stroke risk. 2,16 The slope of improvement in anticoagulant use has been static for more than 10 years, improving by 1% per annum to only 50% in 2012. 14,17,18 Undertreatment at older ages persists in more recent studies.…”
mentioning
confidence: 99%